A major range extension for Carcharhinus altimus (Springer, 1950) in the South Pacific Ocean - Duffy, Clinton A. J.; Struthers, Carl D. (Zootaxa, 2017)
The occurrence of the bignose shark Carcharhinus altimus at Ducie Island, Pitcairn Islands is reported for the first time based upon re-identification of four museum voucher specimens. The presence of a pregnant female and a juvenile confirms C. altimus breeds at Ducie Island and should be considered resident there. The specimens had been misidentified as the grey reef shark, C. amblyrhynchos, emphasising the ongoing value of collecting museum voucher specimens of supposedly common species. The occurrence of C. altimus at Ducie Island suggests resident populations of C. altimus are likely to occur throughout the tropical and subtropical Pacific Ocean but may have been overlooked due to their preference for deep demersal habitats during the day, or misidentification as other Carcharhinus species.